2020
DOI: 10.1002/sstr.202000101
|View full text |Cite
|
Sign up to set email alerts
|

Elemental 2D Materials: Progress and Perspectives Toward Unconventional Structures

Abstract: Elemental 2D materials have attracted a great deal of interest due to their excellent properties for various applications in catalysis, sensing, photonics, intracellular gene regulation, magnetism, superconductivity, and so on. It is broadly accepted that the physicochemical properties are highly associated with their atomic arrangements and coordination. Recent studies have demonstrated that unconventional structures of elemental 2D materials exhibit unexpected physicochemical properties and innovative applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…61,62 , elemental 2D materials (e.g., black phosphorus (BP), tellurium, silicene, germanene, borophene, etc.) [63][64][65] , layered metal oxides 66,67 , layered double hydroxides (LDHs) 68,69 , graphitic carbon nitride (g-C3N4) 70,71 , MXenes 72 , metals 73 , organics/polymers 74,75 , metal-organic frameworks (MOFs) 76,77 , covalent-organic frameworks (COFs) 78,79 , organic-inorganic hybrid perovskites [80][81][82] , and transition metal halides 83,84 , have been synthesized by various synthetic methods in the last decade. It is worth pointing out that the number of materials in the family of 2D materials is still continuously growing every year.…”
Section: Introductionmentioning
confidence: 99%
“…61,62 , elemental 2D materials (e.g., black phosphorus (BP), tellurium, silicene, germanene, borophene, etc.) [63][64][65] , layered metal oxides 66,67 , layered double hydroxides (LDHs) 68,69 , graphitic carbon nitride (g-C3N4) 70,71 , MXenes 72 , metals 73 , organics/polymers 74,75 , metal-organic frameworks (MOFs) 76,77 , covalent-organic frameworks (COFs) 78,79 , organic-inorganic hybrid perovskites [80][81][82] , and transition metal halides 83,84 , have been synthesized by various synthetic methods in the last decade. It is worth pointing out that the number of materials in the family of 2D materials is still continuously growing every year.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Moreover, it was theoretically confirmed that some of the 1D vdW materials exhibit thickness-dependent properties, such as the bandgap expansion with the indirect-to-direct transition as the number of unit chains decrease from their bulk crystal, similar to well-studied transition metal dichalcogenides (TMDs). [22][23][24][25] Based on this aspect, numerous studies have been conducted to utilize 1D nanowires in functional electronic devices such as FET [26][27][28][29] and photodetectors, [30][31][32][33] but diversity among promising materials is still limited. Therefore, it is necessary to discover new types of 1D materials, verify their electronic properties, and expand the potential candidates for future electronic device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Borophene manifested improved tunable properties among chemically similar structures described by anisotropy and polymorphism. 99 In a general sense, numerous common aspects are shown by these polymorphs. Particularly, most of the structural prototypes of borophene are found to be metallic and have excellent optical transparency and mechanical strength.…”
Section: Synthesis Of a 2d Borophene Flatlandmentioning
confidence: 99%